The Effect of Financial Performance and Environmental Sensitivity on ESG Disclosure: Empirical Study in Agroindustrial Sector - Markus Apriono; Isti Fadah; Siti Maria Wardayati; Regina Niken; Bayu Aprillianto; Nining Ika Wahyuni; Intan Awwaliyah (AIBPM Publisher, 2023)
Environmental, Social, Governance (ESG) has become an essential issue in business operation as a result from pressures from stakeholder such as government, society, creditors, and investors not to only seeking profit, but also preserving the environment, caring the society, and having good governance. The purpose of this study is to examine the effect of financial performance and environmental sensitivity on ESG implementation by using regression model. The financial performance measured by Return on Asset (ROA), environmental sensitivity measured by dummy variable which divided companies into two groups with high and low Green House Gas (GHG), and ESG disclosure measured by ESG indicators. There were 18 agroindustrial companies listed in Indonesia Stock Exchange from 2019-2021 observed. The result of this study showed that there was no significant effect of financial performance measured by Return on Asset (ROA) on ESG, otherwise there was positive significant influence of environmental sensitivity on ESG.